Determinants of Prosocial Behavior in Included Versus Excluded Contexts - Cuadrado, Esther; Tabernero, Carmen; Steinel, Wolfgang (Frontiers in Psychology, 2016)
Prosocial behavior is increasingly becoming necessary as more and more individuals experience exclusion. In this context it is important to understand the motivational determinants of prosocial behavior. Here we report two experiments which analyzed the influence of dispositional (prosocialness; rejection sensitivity) and motivational variables (prosocial self-efficacy; prosocial collective efficacy; trust; anger; social affiliation motivation) on prosocial behavior under neutral contexts (Study 1), and once under inclusion or exclusion conditions (Study 2). Both studies provided evidence for the predicted mediation of prosocial behavior. Results in both neutral and inclusion and exclusion conditions supported our predictive model of prosocial behavior. In the model dispositional variables predicted motivational variables, which in turn predicted prosocial behavior. We showed that the investigated variables predicted prosocial behavior; this suggests that to promote prosocial behavior one could (1) foster prosocialness, prosocial self and collective efficacy, trust in others and affiliation motivation and (2) try to reduce negative feelings and the tendency to dread rejection in an attempt to reduce the negative impact that these variables have on prosocial behavior. Moreover, the few differences that emerged in the model between the inclusion and exclusion contexts suggested that in interventions with excluded individuals special care emphasis should be placed on addressing rejection sensitivity and lack of trust.